2006
DOI: 10.1007/s10072-006-0607-x
|View full text |Cite
|
Sign up to set email alerts
|

Two new families with hereditary essential chin myoclonus: clinical features, neurophysiological findings and treatment

Abstract: Hereditary essential chin myoclonus (HECM) is a rare movement disorder characterised by involuntary and irregular twitches of the chin. It can be considered a benign, focal variant of hereditary essential myoclonus. We studied two families that had several members suffering from HECM. Both families showed an autosomal dominant transmission with incomplete penetrance. Extensive neurophysiological studies were carried out on three patients. The results confirmed the myoclonic nature of phenotypical appearance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Its low frequency, however, the occurrence during sleep and the lack of an association with rest, posture, and action, which are used to categorize the different types of tremor,5 argue against this label. In agreement with other authors,8 our findings do not support a classification of geniospasm as myoclonus either. In contrast to the brief duration of bursts (10–25 milliseconds) described in other cases,9, 10 the paroxysmal activity that we saw lasted up to 3 seconds and we could not register any cortical potentials in standard EEG preceding mentalis muscle activity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Its low frequency, however, the occurrence during sleep and the lack of an association with rest, posture, and action, which are used to categorize the different types of tremor,5 argue against this label. In agreement with other authors,8 our findings do not support a classification of geniospasm as myoclonus either. In contrast to the brief duration of bursts (10–25 milliseconds) described in other cases,9, 10 the paroxysmal activity that we saw lasted up to 3 seconds and we could not register any cortical potentials in standard EEG preceding mentalis muscle activity.…”
Section: Discussionsupporting
confidence: 84%
“…From experimental studies in the monkey that demonstrate a strictly ipsilateral nuclear origin of the motoneurons of the mentalis muscle,11 we had earlier concluded that the site of origin of geniospasm, which symmetrically affects the mentalis muscles on both sides, should be sought either within the muscle itself or in neuronal structures superordinate to both facial nerve nuclei. This assumption has been supported by detailed observations of Devetag Chalaupka et al,8 showing that reticular inhibition/disinhibition phenomena are more likely to cause the disorder than are nuclear or peripheral structures.…”
Section: Discussionmentioning
confidence: 70%
“…The amplitude is variable and the tremor frequency varies between 2 and 11 Hz. It has been argued that neurophysiological evidence support the movements as fast, jerk-like with an irregular frequency, and thus it might be better classified as myoclonus rather than an orolingual tremor 21 42. The movements are generally considered benign with little interference with speech, drinking or sleep, although exceptions have been described.…”
Section: Unusual Tremor Syndromesmentioning
confidence: 99%
“…They may cause social embarrassment, which is the typical reason for seeking medical attention. Associated conditions have also been described, such as tongue biting, myoclonus, nystagmus, nocturnal bruxism, rapid eye movement sleep behavioural disorder, otosclerosis, familiar neuropathies and Parkinson's disease 41 42. Pharmacological therapies, such as benzodiazepines, haloperidol, phenytoin and hydroxyzine hydrochloride, have usually shown a poor response 41.…”
Section: Unusual Tremor Syndromesmentioning
confidence: 99%
“…A considerable amount of literature has been published on BTA treatment of the mentalis. It can be used in the treatment of chin asymmetric ptosis, mentalis spasm, skin dimpling, and hereditary essential chin myoclonus . It is also prevalent in combination use with implants or fillers for chin rejuvenation, and it has been confirmed to result in better outcomes than either alone …”
Section: Discussionmentioning
confidence: 99%